Methodological challenges in neuropolitical research and determining the sample selection - Orhan, Ertuğrul Buğra (IGI Global, 2024)
The burgeoning field of neuropolitics, scrutinizing the intersection of neurological data and political behavior, is gaining traction in interdisciplinary research. This study navigates challenges, methodological advancements, and opportunities in this domain, focusing on data collection tools and integrating qualitative methods. Highlighting neuropolitics' multidisciplinary essence and reliance on EEG, fMRI, and Eye Trackers, the paper delves into decision-making behaviors. It emphasizes the need for standardized research processes and explores the efficacy of these tools, spotlighting EEG's accessibility and the user-friendliness of Eye Trackers. The study links neuropolitics with qualitative methodologies, advocating for sample coherence and employing data triangulation for rigor. It proposes a preliminary model integrating qualitative frameworks and neurological tools, accentuating their potential in enhancing objectivity. It urges collaborative efforts to challenge conventional paradigms in political studies. © 2024, IGI Global. All rights reserved.